2020
DOI: 10.1136/bmjopen-2019-035887
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided bilateral pudendal nerve blocks of nulliparous women with epidural labour analgesia in the second stage of labour: a randomised, double-blind, controlled trial

Abstract: ObjectiveTo explore whether an ultrasound-guided pudendal nerve block (PNB) could decrease anaesthetic use, thereby shortening the length of the second stage of labour in women undergoing epidural analgesia.DesignProspective, single-centre, randomised, double-blind, controlled trial.SettingAn obstetric centre in a general hospital in China.Participants72 nulliparous women were randomised, and 71 women completed the study.InterventionAn ultrasound-guided bilateral PNB was administered to all study participants;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…e incidence of complications in the experimental group was significantly lower than that in the control group, but the maternal satisfaction was much higher than that in the control group (P < 0.05). Studies pointed out that pudendal nerve block may cause pelvic muscle relaxation, accelerate the progress of the second stage of labor, and shorten the time of the second stage of labor [18]. However, Kwon et al [19] mentioned in the article that the time of the second stage of labor was related to many factors, such as maternal age, fetal position, and baby weight.…”
Section: Discussionmentioning
confidence: 99%
“…e incidence of complications in the experimental group was significantly lower than that in the control group, but the maternal satisfaction was much higher than that in the control group (P < 0.05). Studies pointed out that pudendal nerve block may cause pelvic muscle relaxation, accelerate the progress of the second stage of labor, and shorten the time of the second stage of labor [18]. However, Kwon et al [19] mentioned in the article that the time of the second stage of labor was related to many factors, such as maternal age, fetal position, and baby weight.…”
Section: Discussionmentioning
confidence: 99%
“…A successful pudendal nerve block is crucial for the diagnosis of pudendal neuralgia and provides guidance for treatment. Different studies, including two randomized controlled trials, demonstrated the absence of complications for this procedure [ 5 , 16 21 ]. Furthermore, no significant difference in terms of efficacy was demonstrated between US and fluoroscopic guidance.…”
Section: Resultsmentioning
confidence: 99%
“…One older randomized study suggested that spinal analgesia was superior to PNB for operative vaginal delivery 9 . In contrast, a recent randomized study suggests that ultrasound-guided bilateral PNB may serve as an additional, effective adjunct method of labor analagia 8 . The Cochrane review on analgesia for forceps delivery concluded that there is insufficient evidence to support any particular analgesic agent or method as the most effective in providing pain relief for forceps delivery 10 .…”
Section: Introductionmentioning
confidence: 92%
“…The use of PNB decreased as epidural and spinal analgesia became readily available 3 . The evidence is contradictory on the value or necessity of PNB in addition to epidural or spinal analgesia 8 - 10 . One older randomized study suggested that spinal analgesia was superior to PNB for operative vaginal delivery 9 .…”
Section: Introductionmentioning
confidence: 99%